On phase, action and canonical conservation laws in kinematic-wave theory - Maugin, Gerard A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Canonical equations of energy and momentum are constructed in the kinematic-wave theory of waves ina continuum. This is done in analogy with what is achieved in nonlinear continuum mechanics. The starting point is a generalized balance of wave action. The standard formulas are recovered when the system follows from the averaged-Lagrangian variational formulation of Whitham.